Internal Rent Capture and the Profit-Concentration Relation - Bradburd, Ralph; Pugel, Thomas; Pugh, Katrina (The Review of Economics and Statistics, 1991)
If labor is able to capture a portion of the economic rents in profitable industries, industry profitability and the relation between market structure and profitability may both be mismeasured. This paper estimates a simultaneous equation system in which both the price-cost margin and compensation per worker (including fringe benefits) are endogenous variables. The authors' sample consists of eighty-five well-defined producer goods industries. They find that labor compensation does include some capture of economic rents. Further, when they correct for this rent capture, the relation between market concentration and the price-cost margin is strengthened significantly. Copyright 1991 by MIT Press.